"Do you dive?": Methodological considerations for engaging with "volume". Issue 7 (July 2017) - Squire, Rachael
Abstract: The idea that we inhabit three dimensions is clearly not new, yet the explicit articulation of "volume" in recent literature has proved to be an extremely useful means through which to produce novel insights into the conduct and practice of geopolitics. Although the value of engaging with "volume" has been well established and taken discussions in new directions, yet the practicalities of doing this research are yet to be considered in great detail. How methodologically do we approach the three‐dimensional within political geography? Although this paper does not seek to outline a methodological framework, it draws on my own research to prompt discussion about the role of "immersive" methodologies in generating different perspectives within political geography. The paper ends by suggesting that a stronger interface between political geography and methodologies utilised in other geographical subdisciplines might be useful in producing novel insights into the earth's geopolitical volumes.